PENGARUH MEDIA AUDIO DAN VIDEO TERHADAP MAHASISWA PROGRAM STUDI FARMASI DALAM KEMAMPUAN BERBICARA DI INSTITUT KESEHATAN DELI HUSADA DELI TUA - Mona Fitri Gurusinga (Jurnal Penelitian Farmasi & Herbal, 2019)
This study aims to find out: whether the use of video is more effective than using audio inimproving students' pharmacists 'speaking skills. Find out whether the use of video is moreeffective than general media use in improving students' speaking skills. Whether audio usage moreeffective rather than using conventional media in improving students 'speaking skills. Find outwhich media is the most effective among the use of Video, Audio, and conventional media onimproving students' speaking skills. This research is an experimental study using Quasi PretestPost-test Control Group design. The research sample was students pharmacist class 1A, 1B, and1C taken by a simple cluster random sampling technique. This research shows that video usage isthe most effective medium among all of them, and the use of video is more effective than usingaudio in improving students ' speaking skills.